The Legal Impact on People Died in Kasepekang Sanction - Ni Made Trisna Dewi (Sociological Jurisprudence Journal, 2021)
The Pakraman village is led by village officers. The issue of how to implement the Kasepekang sanction is very important to analyse because fraud or abuse of power often occurs in this sector. Kesepekang the term of traditional sanctions in the form of a temporary dismissal as a member of the banjar and pakraman villages. Those affected by this sanction are not entitled to receive banjar service / assistance and pakraman villages. This type of research is empirical legal research oriented to the collection of empirical data in the field. Based on this empirical data the researcher conducted an in-depth analysis in accordance with the relevant theory to make conclusions. Kasepekang sanctions are given because community members do not want to solve and conduct paruman to find solutions to adat problems. Based on paruman adat leaders and community representatives prescribed on Awig-awig Number 18, paragraph 14 regarding unwritten regulations, it was decided by the village of Pakraman Pempatan and it was agreed that the person be subject to a sanction of being left unchecked. This case was motivated by civil problems continued with the existence of actions and reactions, developed into a criminal problem that is the desecration of the holy place and customary matters.